Perinatal risk factors of neurodevelopmental impairment after fetoscopic laser photocoagulation for twin–twin transfusion syndrome: systematic review and meta‐analysis. (1st November 2021) - Hessami, K.; Nassr, A. A.; Sananès, N.; Castillo, J.; Castillo, H. A.; Sanz Cortes, M.; Espinoza, J.; Donepudi, R. V.; Sun, R. C.; Krispin, E.; Belfort, M. A.; Shamshirsaz, A. A.
ABSTRACT: Objective: Monochorionic twins with twin–twin transfusion syndrome (TTTS) treated with fetoscopic laser photocoagulation (FLP) are at increased risk of neurodevelopmental impairment (NDI). This meta‐analysis aimed to identify the prevalence of and perinatal risk factors for NDI in TTTS survivors treated with FLP. Methods: We performed a search in PubMed, EMBASE, Scopus and Web of Science, from inception to 13 February 2021, for studies evaluating perinatal risk factors for NDI in children diagnosed prenatally with TTTS managed by FLP. Data on severity of TTTS at the time of diagnosis, defined according to the Quintero staging system, FLP‐related complications and perinatal outcomes were compared between children with a history of TTTS treated with FLP with and those without NDI, which was defined as performance on a cognitive or developmental assessment tool ≥ 2 SD below the mean or a defined motor or sensory disability. A random‐effects model was used to pool the mean differences or odds ratios (OR) with the corresponding 95% CIs. Heterogeneity was assessed using the I 2 statistic. Results: Nine studies with a total of 1499 TTTS survivors were included. The overall incidence of NDI was 14.0% (95% CI, 9.0–18.0%). The occurrence of NDI in TTTS survivors was associated with later gestational age (GA) at FLP (mean difference, 0.94 weeks (95% CI, 0.50–1.38 weeks); P < 0.0001, I 2 = 0%), earlier GA at delivery (mean difference, –1.44 weeks (95% CI, –2.28 to –0.61 weeks); P = 0.0007, I 2 = 49%) and lower birth weight (mean difference, –343.26 g (95% CI, –470.59 to –215.92 g); P < 0.00001, I 2 = 27%). Evaluation of different GA cut‐offs showed that preterm birth before 32 weeks was associated with higher risk for NDI later in childhood (OR, 2.25 (95% CI, 1.02–4.94); P = 0.04, I 2 = 35%). No statistically significant difference was found between cases with and those without NDI with respect to Quintero stage of TTTS, recipient or donor status, development of postlaser twin anemia–polycythemia sequence, recurrence of TTTS and incidence of small‐ for‐gestational age or cotwin fetal demise. Conclusions: TTTS survivors with later GA at the time of FLP, earlier GA at delivery and lower birth weight are at higher risk of developing NDI. No significant association was found between Quintero stage of TTTS and risk of NDI. Our findings may be helpful for parental counseling and highlight the need for future studies to understand better the risk factors for NDI in TTTS survivors. © 2021 International Society of Ultrasound in Obstetrics and Gynecology. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Factores de riesgo perinatales de trastorno del desarrollo neurológico después de la fotocoagulación fetoscópica con láser para el síndrome de transfusión feto‐fetal: revisión sistemática y metaanálisis Objetivo: Los gemelos monocoriónicos con síndrome de transfusión feto‐fetal (STFF) tratados con fotocoagulación fetoscópica con láser (FFL) tienen un mayor riesgo de trastorno del desarrollo neurológico (TDN). El objetivo de este metaanálisis fue identificar la prevalencia y los factores de riesgo perinatales de TDN en los supervivientes del STFF tratados con FFL. Métodos: Se realizó una búsqueda en PubMed, EMBASE, Scopus y Web of Science, desde el inicio hasta el 13 de febrero de 2021, de estudios que hubieran evaluado los factores de riesgo perinatales para el TDN en niños diagnosticados prenatalmente con STFF tratados con FFL. Se compararon los datos sobre la gravedad del STFF en el momento del diagnóstico, definida según el sistema de estadificación de Quintero, las complicaciones relacionadas con la FFL y los resultados perinatales entre los niños con antecedentes de STFF tratados con FFL y los que no tenían TDN, que se definió como el resultado en una herramienta de evaluación cognitiva o del desarrollo ≥2 DE por debajo de la media o una discapacidad motora o sensorial definida. Se utilizó un modelo de efectos aleatorios para combinar las diferencias de medias o las razones de momios (RR) con los correspondientes IC 95%. La heterogeneidad se evaluó mediante el test estadístico I2. Resultados: Se incluyeron nueve estudios con un total de 1499 supervivientes de STFF. La incidencia total de TDN fue del 14, 0% (IC 95%, 9, 0–18, 0%). La presencia de TDN en supervivientes del STFF se asoció con una edad gestacional (EG) más tardía en el momento de la FFL (diferencia media, 0, 94 semanas (IC 95%, 0, 50–1, 38 semanas); P<0, 0001, I2 =0%), una EG más temprana en el momento del parto (diferencia media, ‐1.44 semanas (IC 95%, ‐2, 28 a 0, 61semanas); P=0, 0007, I2 =49%) y menor peso al nacer (diferencia media, ‐343, 26 g (IC 95%, ‐470, 59 a ‐215, 92 g); P<0, 00001, I2 =27%). La evaluación de diferentes umbrales de la EG mostró que el parto pretérmino antes de las 32 semanas estuvo asociado con un mayor riesgo de TDN más adelante en la infancia (RM, 2, 25 (IC 95%, 1, 02–4, 94); P=0, 04, I2 =35%). No se encontraron diferencias estadísticamente significativas entre los casos con y sin TDN con respecto al estadio de Quintero del STFF, el estado del receptor o del donante, el desarrollo de la secuencia postláser de anemia‐policitemia de los gemelos, la recurrencia del STFF y la incidencia de la edad gestacional pequeña o la muerte fetal de un gemelo. Conclusiones: Los supervivientes del STFF con una EG más tardía en el momento de la FFL, una EG más temprana en el momento del parto y un menor peso al nacer tienen un mayor riesgo de desarrollar un TDN. No se encontró una asociación significativa entre el estadio de Quintero del STFF y el riesgo de TDN. Estos hallazgos pueden ser útiles para el asesoramiento de los padres y ponen de relieve la necesidad de realizar estudios futuros para comprender mejor los factores de riesgo de TDN en los supervivientes del STFF. © 2021 International Society of Ultrasound in Obstetrics and Gynecology. 摘要: 对双胎输血综合征进行胎儿镜引导激光治疗后造成神经发育损害的围产期风险因素:系统评价与meta分析 目的: 对患有双胎输血综合征(TTTS)的单绒毛膜双胎采取胎儿镜引导激光治疗(FLP)会增加神经发育损害(NDI)的风险。本meta分析目的在于识别出经FLP治疗的TTTS幸存者的NDI患病率及围产期风险因素。 方法: 我们在PubMed数据库、荷兰医学文摘数据库(EMBASE)、斯高帕斯数据库(Scopus)和科学引文索引数据库(Web of Science)上进行了一次搜索，从开端到2021年2月13日，搜索了对产期诊断为TTTS并经FLP治疗出现NDI的围产期风险因素评估的研究。诊断时TTTS的严重程度数据是依据Quintero分级系统界定的，将FLP相关并发症及围生结局在有TTTS病史、经FLP治疗后有NDI和无NDI的儿童之间进行了对比，NDI是以对一个认知或发育评估工具≥2 SD 低于平均数的表现，或是以一个确定的运动或知觉障碍来界定的。采用一个随机效应模型来集中平均差或比值比(OR)，相应的可信区间(CI)为95%。采用I2统计量来评估异质性。 结果: 本研究包含九项研究，总共1499名TTTS幸存者。NDI的总发病率为14.0%(95% CI，9.0–18.0%)。TTTS幸存者中NDI的发生与FLP时胎龄较晚(平均差，0.94周(95%CI, 0.50–1.38周)；P<0.0001, I2 =0%)、分娩时胎龄较早(平均差，–1.44周(95%CI，–2.28 至 0.61周)；P=0.0007, I2 =49%)以及较低出生体重(平均差，–343.26克(95%CI，–470.59 至–215.92克)有关。对不同胎龄界限的评估表明，孕32周前早产与以后在童年时期出现NDI的较高风险相关联(OR，2.25(95%CI，1.02–4.94)；P=0.04，I2 =35%)。在TTTS的Quintero分级、受体或供体状况、激光治疗后双胎贫血红细胞增多序列症的发展、TTTS的复发，以及小于胎龄的发病率或双胎死亡方面，在有NDI和无NDI的病例之间没有发现显著的统计差异。 结论: FLP时胎龄较晚、分娩时胎龄较早和较低出生体重的TTTS幸存者，有发展出NDI的更高风险。TTTS的Quintero分级与NDI风险之间未发现重大关联。我们的研究结果有助于双亲心理咨询，强调未来研究的必要性，从而更好地理解TTTS幸存者中发展出NDI的风险因素。© 2021年国际妇产科超声学会。